Effect of Entrepreneurial Innovativeness Orientation, Product Innovation, and Value Co-Creation on Marketing Performance - Killa, Maklon Felipus (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
The aim of this study is to analyze the effect of entrepreneurial innovativeness orientation, product innovation, and value co-creation on marketing performance. Handicraft firms in Indonesia used as a sample. Sampling was done using purposive sampling technique. Data were collected using a questionnaire given directly to the respondent. The total data that can be further analyzed as much as 192 respondents. Data analysis using Structural Equation Modelling - SEM with the AMOS program assistance. The results showed that the entrepreneurial innovativeness orientation has significant effect on product innovation. In addition, product innovation and value co-creation have a significant effect on marketing performance, and value co-creation to be a mediator in the relationship of product innovation and marketing performance.